Potret Pemimpin Kristen Sebagai Sumber Daya Manusia Unggul Menurut Kitab Titus - Iksantoro Iksantoro (Jurnal Teologi Berita Hidup, 2019)
Theological Seminary as an Indonesian Christian Religious Higher Education Institution has the task of preparing Excellent Christian Leaders, so they can compete on the global stage. The Titus letter is one of the books that offers a image of a Excellent Christian Leader. Understanding and making such Christian leaders can help the government's vision of preparing Excellent Human Resources. The image of a Excellent Christian Leader according to Titus must have certain qualifications are family qualifications (Tit. 1: 6), personality qualifications (Tit. 1: 7), social qualifications (Tit. 1: 8), spiritual qualifications (Tit. 1: 8, 9) and professional qualifications (Tit. 1: 9, 13; 2: 1). AbstrakSekolah Tinggi Teologi sebagai Lembaga Pendidikan Tinggi Keagamaan Kristen Indonesia mengemban tugas untuk mempersiapkan para pemimpin Kristen yang unggul, sehingga dapat bersaing di kancah global. Surat Titus merupakan salah satu kitab yang menyodorkan potret Pemimpin Kristen yang unggul. Dengan memahami dan mencetak pemimpin Kristen yang demikian, dapat menolong visi pemerintah menyiapkan Sumber Daya Manusia Unggul. Potret pemimpin Kristen yang unggul menurut Titus harus memiliki kualifikasi tertentu, yaitu kualifikasi keluarga (Tit. 1:6), kualifikasi kepribadian (Tit. 1:7), kualifikasi sosial (Tit. 1:8), kualifikasi spiritual (Tit. 1:8, 9) dan kualifikasi professional (Tit. 1:9, 13; 2:1).